From open-shell singlet diradicaloids to polyradicaloids - Gopalakrishna, Tullimilli; Zeng, Wangdong; Lu, Xuefeng; Wu, Jishan (Chemical communications (Cambridge, England), 2018)
In this Feature Article , we highlight our recent efforts toward stable open-shell singlet diradicaloids and polyradicaloids. A brief review on the historical works in the area is introduced first, followed by discussion on the fundamental electronic and physical properties of open-shell singlet diradicaloids. Then, the structure-diradical character relationships based on our recently developed diradicaloids are presented. Next, the challenges and solutions toward stable polyradicaloids and 3D π-conjugated diradicaloids are discussed. Finally, their preliminary material applications are introduced and a perspective view of the area is given. We highlight our recent studies on stable open-shell singlet diradicaloids and polyradicaloids, originating from Chichibabin's hydrocarbon reported 110 years ago.